Changes in pain perception in women undergoing Breast Screening Mammograms: a Study based on Breast structure. - Esposito, Deborah; Ludeno, Carmen; Marinelli, Simona; Bertoldi, Anna; Selvestrel, Valeria; Giannattasio, Marianna; Rizzari, Lauretta; Marra, Vincenzo; Milanesio, Luisella; Frigerio, Alfonso; Luparia, Andrea; Aiello, Adriana; et al. (Journal of Biomedical Practitioners, 2025)
INTRODUCTION The study involved 100 women taking part to a Breast Screening session carried out by one Mammographer. Participants answered a questionnaire related to pain perception experienced during the mammogram. Breast density has been detected by Quantra Software. The study aims to explore the potential association between breast density, breast thickness and pain perception experienced during the Mammogram. Quality technical standards have been evaluated by two technical experts of Referring Regional Mammography Centers of Turin. MATERIALS AND METHODS Pain, in order to be detected, has been measured through the Visual Analogical Scale. Breast examinations have been performed using a digital Mammo-Machine, while density was evaluated using Quantra software. A Systematic Literature Review about the subject has been carried out. RESULTS Results demonstrated that the average pain perception was light-moderate, and mainly due to the compression applied during the Mammogram. It was observed that Women with higher breast density experienced more pain than women with less density; however, no correlation was found between pain and breast thickness. CONCLUSIONS The study observes that pain perception during mammography is not solely dependent on subjective factors, such as psychological influences, but is also affected by breast density. Indeed, higher densities are associated to higher pain. However, no direct correlation between pain and breast thickness was identified. The finding suggests that a subjective component plays a significant role in pain perception.